Velocity and Pressure Analysis in a Divergent Area Fitted with Dimpled Hub - Sabah Shukri Askari, Ehan; Wisnoe, Wirachman; ., . (International Journal of Engineering and Technology, 2018)
A diffuser fitted with turbulators is able to enhance the distribution of both velocity and pressure. This research presents a numerical analysis for an annular diffuser type with dimpled hub. The diffuser is used to increase the static pressure by consuming kinetic energy. Three different hub models which are straight dimpled hub (SDH), divergent dimpled hub (DDH) and cone dimpled hub (CDH) are simulated to study their effects on the velocity and pressure profile for an annular diffuser. Results indicate that the insertion of the three dimpled hub models enhances velocity and pressure distribution through the diffuser. Numerical results recorded that the velocity disturbance enhanced up to 10%, 20% and 4% for the SDH, DDH, and CDH, respectively compared with the diffuser without dimples. Furthermore, the results show that the velocity distribution is the best with SDH model and the static pressure with CDH is the largest.Â Â